IMPLEMENTASI EDMS DALAM PENATAAN DOKUMEN DI RAIL DOCUMENT SYSTEM PT. KERETA API INDONESIA (PERSERO) DAERAH OPERASI 1 JAKARTA - Ismail, Fahmi; Iswary Lawanda, Ike (BACA: Jurnal Dokumentasi dan Informasi, 2020)
To ensure the availability of information needed by employees of PT KAI (Persero) Operating Area 1, EDMS becomes a solution that utilizes information technology and communication in its management. This research uses a qualitative approach with descriptive case study research method. The research data was obtained through observation, interviews and document studies. The results of this study indicate that the implementation of EDMS in structuring documents of PT KAI Daerah Operasi 1 Jakarta using the Rail Document System serves to cut time in the bureaucratic process; saving resources; and more efficient and effective access. This can be reflected in the findings obtained by researchers indicating that these components have been implemented in electronic document processing activities, although in practice there are still things that need to be improved to improve the effectiveness and efficiency of the RDS system.